2018
DOI: 10.1002/adma.201707025
|View full text |Cite
|
Sign up to set email alerts
|

Porous Graphene Films with Unprecedented Elastomeric Scaffold‐Like Folding Behavior for Foldable Energy Storage Devices

Abstract: The development of fully foldable energy storage devices is a major science and engineering challenge, but one that must be overcome if next-generation foldable or wearable electronic devices are to be realized. To overcome this challenge, it is necessary to develop new electrically conductive materials that exhibit superflexibility and can be folded or crumpled without plastic deformation or damage. Herein, a graphene film with engineered microvoids is prepared by reduction (under confinement) of its precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
63
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 52 publications
(59 reference statements)
2
63
2
Order By: Relevance
“…Moreover, the RGO can be folded back and forth at exactly the same position multiple times, suggesting its good flexibility. Huang et al [161] also demonstrated that the RGO is ultraflexible which can be single folded, double folded and crumpled, but springs back to its original shape without yielding or plastic deformation after removing the applied stress. Due to existence of defects and functional groups, the GO shows intrinsic wrinkles.…”
Section: Out-of-plane Mechanicsmentioning
confidence: 99%
“…Moreover, the RGO can be folded back and forth at exactly the same position multiple times, suggesting its good flexibility. Huang et al [161] also demonstrated that the RGO is ultraflexible which can be single folded, double folded and crumpled, but springs back to its original shape without yielding or plastic deformation after removing the applied stress. Due to existence of defects and functional groups, the GO shows intrinsic wrinkles.…”
Section: Out-of-plane Mechanicsmentioning
confidence: 99%
“…Raman spectra were further used to characterize the chemical reduction and structural information of the rGO. [6,40] The high I D /I G value indicates the high graphitization degree to favorably enhances the conductivity of the rGO, [41] which would play an imperative role in flexible electronics. [6,40] The high I D /I G value indicates the high graphitization degree to favorably enhances the conductivity of the rGO, [41] which would play an imperative role in flexible electronics.…”
Section: Structural Characterizationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The mechanical property of this 3D architecture is highly dependent not only on its constituent materials but also on its geometrical configuration. [1][2][3][4][5][6][7][8][9][10] The mechanical property of this 3D architecture is highly dependent not only on its constituent materials but also on its geometrical configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Wearable electronics with stretchable and foldable features are currently spotlighted as a next‐generation electronics . In particular, they have attracted the attention of many people, in that they could be exploited as potential applications designed to fulfill diverse purposes, such as the detection of human motion, monitoring personal activities and health or for enjoying sports, by using the electrical characteristics of stretchable strain sensors, one of the important applications of wearable electronics, of which the output signals are varying, according to the degree of mechanical deformation …”
Section: Introductionmentioning
confidence: 99%